(untitled) (Jurnal Geomine, 2016)
Value BS&W and °API oil is a major determinant of the quality and quantity of petroleum, where to look for the value to go through several stages and laboratory testing. The purpose of this study was to determine the quality and quantity of oil from several oil tank sample taken. The method used to determine the quality of petroleum using interpolation tables 5 and 6 in the standard book pertamina oil. The necessary data including data BS&W, °API and temperature. Medium The method for determining the quantity of petroleum using NETT value. The results showed 8 tanks taken from a sample, known to tank 5C is disable with the standart and will be retreatment, because the liquid in the tank still contains water 144.67 Bbls and BS&W content above 0.50%. In general, the oil in the research area of oil quality being classified as °API oil stands at 29.7. total NETT 185,775.00 Bbls.